The Role of Self-Reporting in the Evaluation and Diagnosis of Concussion Among National Football League Players - Hayden K. Giuliani-Dewig; Riju Shrestha; Erin B. Wasserman; Christina D. Mack; Gary Solomon; Douglas P. Terry; Javier F. Cárdenas; Allen Sills (Clinical Journal of Sport Medicine, 2026)
Objective: To determine the role of player self-report in concussion evaluation and diagnosis. Design: Retrospective; cross-sectional. Setting: National Football League (NFL). Participants: National Football League players between 2018 and 2023. Interventions: Unaffiliated Neurotrauma Consultant gameday reports; Electronic Medical Records; Game Statistics and Information System. Main Outcome Measures: Concussion evaluations and diagnoses; concussion evaluation trigger; player demographics and characteristics (eg, age, injury history). Results: From 2018 to 2023, player self-report occurred in 24% (preseason) and 30% (regular season) of all concussion evaluations and 32% (preseason) and 39% (regular season) of diagnosed concussions. The proportion of self-report was largest among individuals with 6 to 10 years of NFL experience, offensive and defensive linemen, and those with 2 or more previous concussions. Conclusions: This study found that NFL players self-report concussion-like symptoms to initiate evaluation approximately one-third of the time, which increased to almost 40% in concussed players. This may indicate enhanced improvement in player understanding of the injury and motivation to report to improve their symptoms, which is supported by the finding that players with more experience in the NFL and those with multiple previous concussions showed a higher percentage of triggering the evaluation by self-report. These findings help inform future educational efforts to promote timely reporting and improve postinjury recovery.